Analisis Pengaruh Past Visit, Sense of Place, Attachment to Place dan Novelty Seeking terhadap Minat Kunjung Ulang Wisatawan (Revisit Intention) ke Kampuang Sarosah Harau - Dian Oktavina; Siska Febriyanti. S (i-Tourism: Jurnal Pariwisata Syariah, 2026)
The problem in this study lies in the fact that tourist visits over the past five years have tended to decline. This study aims to analyze the influence of past visit, sense of place, attachment to place, and novelty seeking on tourists’ revisit intention to Kampuang Sarosah Harau .This research employs a quantitative method with a sample of tourists who have revisited Kampuang Sarosah Harau . The results show that past visit, sense of place, and attachment to place have no significant effect on revisit intention, while novelty seeking has a positive and significant effect. Simultaneously, all independent variables have a significant effect on revisit intention. These findings emphasize the importance of providing new and unique experiences to encourage tourists’ intention to revisit